Redefining an epitope of a malaria vaccine candidate, with antibodies against the N-terminal MSA-2 antigen of Plasmodium harboring non-natural peptide bonds (2013)
The aim of obtaining novel vaccine candidates against malaria and other transmissible diseases can be partly based on selecting non-polymorphic peptides from relevant antigens of pathogens, which have to be then precisely modified for inducing a protective immunity against the disease. Bearing in mind the high degree of the MSA-221-40 peptide primary structure's genetic conservation among malaria species, and its crucial role in the high RBC binding ability of Plasmodium falciparum (the main agent causing malaria), structurally defined probes based on non-natural peptide-bond isosteres were thus designed. Thus, two peptide mimetics were obtained (so-called reduced amide pseudopeptides), in which naturally made amide bonds of the 30FIN32-binding motif of MSA-2 were replaced with ?-[CH2-NH] methylene amide isostere bonds, one between the F-I and the second between I-N amino acid pairs, respectively, coded as ?-128 ?-130. These peptide mimetics were used to produce poly- and monoclonal antibodies in Aotus monkeys and BALB/c mice. Parent reactive mice-derived IgM isotype cell clones were induced to Ig isotype switching to IgG sub-classes by controlled in vitro immunization experiments. These mature isotype immunoglobulins revealed a novel epitope in the MSA-225-32 antigen and two polypeptides of rodent malaria species. Also, these antibodies' functional activity against malaria was tested by in vitro assays, demonstrating high efficacy in controlling infection and evidencing neutralizing capacity for the rodent in vivo malaria infection. The neutralizing effect of antibodies induced by site-directed designed peptide mimetics on Plasmodium's biological development make these pseudopeptides a valuable tool for future development of immunoprophylactic strategies for controlling malarial infection. © 2013 The Author(s).